Fabrication of Fiber Optic Based Temperature Sensor. (2019) - Narasimman, S.; Harish Babu, K.; Balakrishnan, L.; Meher, S.R.; Sivacoumar, R.; Alex, Z.C.
Abstract: The metal oxide semiconductors (ZnO, SnO2, Al2 O3 and TiO2 ) were synthesized by co-precipitation method. The synthesized nanoparticles were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive spectrometer (EDS) and UV-Visible spectrometer in diffused reflectance (DR) mode. The XRD results stipulated that the ZnO nanoparticle is crystallized in hexagonal wurtzite structure, SnO2 nanoparticles in rutile tetragonal structure, Al2 O3 nanoparticle in rombohedral structure and TiO2 nanoparticle in rutile anatase structure. The SEM investigation affirms that all the synthesized nanopowders are composed of uniformly distributed grains. The UV-Vis spectrum proclaimed that the synthesized nanoparticles having the band gap of 3.2 eV (ZnO), 3.3 eV (SnO2 ) and 3.5 eV (TiO2 ) respectively. The synthesized nanoparticles were replaced with small cladding region of the optical fiber and act as a temperature sensing materials. The temperature sensing characteristics of the synthesized nanoparticles were investigated for broad wavelength range (200-1000 nm). It reveals that the synthesized Al2 O3 nanoparticles were given linear and high sensitivity (∼27) at 697 nm compared with other sensing materials. Further, we have studied the wavelength dependent temperature sensing characteristics of Al2 O3 nanopowders and it show better sensitivity (∼34) in blue wavelength region (450 nm-495 nm).